(3GdebGeI GdUdGMjI aj GdNjd hGdHjWQI hGdaQhSjIs ((3eMeO Hf eMehO GdMHGd s)
(3ChdgG (B:s
(3Qhi Cf Gdedc GdfGUQ GdSdWGf UdGM GdOjf jhSa Hf CjhH QVi Gddg Yfg cGf eMHkG ddLgGO aGJMkG ddHdGO s
(3BNQgG (B:s
(3aHGddg dbO TZafi HebGdg hLGdg hJefjJ SbWkG ef aYGdg hgPG BNQ GdebGeI GdUdGMjI ai GdNjd hGdHjWQI hGdaQhSjI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B81) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs